2015
DOI: 10.1083/jcb.201501046
|View full text |Cite
|
Sign up to set email alerts
|

The caveolin–cavin system plays a conserved and critical role in mechanoprotection of skeletal muscle

Abstract: The caveolar membrane microdomain plays an integral role in stabilizing the muscle fiber surface in mice and zebrafish.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
125
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(138 citation statements)
references
References 59 publications
11
125
1
1
Order By: Relevance
“…However, whether incorporation of caveolae into the sarcolemmal membrane confers protection against membrane stress has not been tested. Consistent with previous reports showing increased susceptibility to acute membrane damage in the absence of caveolae (29,30), we showed that pressure overload-induced loss of caveolae compromises cardiomyocyte membrane integrity. Reminiscent of the effects seen with cardiac-specific Cav3 overexpression in mice (15), Fgf13 KO increased sarcolemmal caveolae density and membrane convolutions, thereby enhancing the reservoir of membrane available for mechanoprotection.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…However, whether incorporation of caveolae into the sarcolemmal membrane confers protection against membrane stress has not been tested. Consistent with previous reports showing increased susceptibility to acute membrane damage in the absence of caveolae (29,30), we showed that pressure overload-induced loss of caveolae compromises cardiomyocyte membrane integrity. Reminiscent of the effects seen with cardiac-specific Cav3 overexpression in mice (15), Fgf13 KO increased sarcolemmal caveolae density and membrane convolutions, thereby enhancing the reservoir of membrane available for mechanoprotection.…”
Section: Discussionsupporting
confidence: 81%
“…For instance, caveolae have been shown to protect against sarcolemmal damage in skeletal muscle during vigorous activity (29), and to mitigate endothelial cell membrane rupture during increased cardiac output (30). In cardiomyocytes, mechanical stretch was shown to increase cell membrane capacitance by recruiting subsarcolemmal caveolae to the plasma membrane (55).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This basic structure has been referred to as a quantal unit (9). However, sub-quantal oligomeric structures of Cav1 have been described in the PM (9), as well as caveolar clusters formed by multiple caveolae in close, diffraction-limited proximity (10) or as larger rosette structures (11).…”
Section: Edited By Dennis R Voelkermentioning
confidence: 99%